Intensive cooling of the reactor wall model when using water soluble solutions - O. V. Vysokomornaya; M. V. Piskunov; A. O. Oparin; A. P. Vergun (Известия высших учебных заведений: Проблемы энергетики)
The paper reports experimental results on the intensive (fast) cooling of 20 mm steel ball heated to 1000 K when immersing in different coolants in 0.003 m3 glass vessel: tap water, seawater with salt concentration y of about 18 g/l, water solution of NaCl with y~27 g/l. By using the high-speed video recording, we study heat and mass transfer on a surface of the heated ball during the cooling. Experiments allow us to conclude that the film boiling on a surface of the metallic ball is almost excluded when using water solutions of salt as coolants. As a result, a cooling time decreases by 2-4 s as compared to the tap water. In addition, when using water solutions of salt, the temperature balance between steel ball and coolant is reached during a minimum time versus the tap water and seawater.